Coping strategies and perceived social support in fibromyalgia syndrome: Relationship with alexithymia. Issue 2 (7th November 2017) - Di Tella, Marialaura; Tesio, Valentina; Ghiggia, Ada; Romeo, Annunziata; Colonna, Fabrizio; Fusaro, Enrico; Geminiani, Giuliano Carlo; Bruzzone, Maria; Torta, Riccardo; Castelli, Lorys
Abstract : Fibromyalgia (FM) is a chronic pain syndrome characterized by high levels of psychological distress and alexithymia, a personality disposition affecting emotional self‐awareness. The main aim of the present study was to investigate for the first time the relationship between alexithymia and coping strategies on the one hand, and alexithymia and perceived social support on the other, in a sample of FM patients. To reach this aim, 153 FM patients completed a battery of tests assessing coping strategies, perceived social support, alexithymia, psychological distress and pain intensity. Four regression analyses were performed to assess whether alexithymia was still a significant predictor of coping strategies and perceived social support, after controlling for psychological distress. High levels of both psychological distress and alexithymia were found in our sample of FM patients. Regarding coping strategies, FM patients reported higher scores on problem‐focused coping, with respect to the other two coping strategies. The regression analyses showed that the externally‐oriented thinking factor of alexithymia significantly explained both problem‐ and emotion‐focused coping, while the difficulty‐describing feelings factor of alexithymia proved to be a significant predictor of perceived social support. Only the variance of dysfunctional coping ceased to be uniquely explained by alexithymia (difficulty identifying feelings factor), after controlling for psychological distress, particularly anxiety. These results highlight a negative relationship between alexithymia and both the use of effective coping strategies and the levels of perceived social support in FM patients. An adequate assessment of both alexithymia and psychological distress should therefore be included in clinical practice with these patients.